Recombinant Acetylcholine Receptor Immunization Induces a Robust Model of Experimental Autoimmune Myasthenia Gravis in Mice - Theissen, Lukas; Schroeter, Christina B; Huntemann, Niklas; Räuber, Saskia; Dobelmann, Vera; Cengiz, Derya; Herrmann, Alexander; Koch-Hölsken, Kathrin; Gerdes, Norbert; Hu, Hao; Mourikis, Philipp; Polzin, Amin; et al. (Cells, 2024)
Myasthenia gravis (MG) is a prototypical autoimmune disease of the neuromuscular junction (NMJ). The study of the underlying pathophysiology has provided novel insights into the interplay of autoantibodies and complement-mediated tissue damage. Experimental autoimmune myasthenia gravis (EAMG) emerged as a valuable animal model, designed to gain further insight and to test novel therapeutic approaches for MG. However, the availability of native acetylcholine receptor (AChR) protein is limited favouring the use of recombinant proteins. To provide a simplified platform for the study of MG, we established a model of EAMG using a recombinant protein containing the immunogenic sequence of AChR in mice. This model recapitulates key features of EAMG, including fatigable muscle weakness, the presence of anti-AChR-antibodies, and engagement of the NMJ by complement and a reduced NMJ density. Further characterization of this model demonstrated a prominent B cell immunopathology supported by T follicular helper cells. Taken together, the herein-presented EAMG model may be a valuable tool for the study of MG pathophysiology and the pre-clinical testing of therapeutic applications.
Keywords: imunizace; Animals; experimentální autoimunitní myasthenia gravis; Complement System Proteins; receptory cholinergní; Immunization; nervosvalové spojení; Neuromuscular Junction; zvířata; Mice; autoprotilátky; Myasthenia Gravis, Autoimmune, Experimental; Autoantibodies; komplement; Receptors, Cholinergic; myši